GLOBALISASI SEBAGAI LANDASAN PENGEMBANGAN KURIKULUM PESANTREN - Rahmat Raharjo (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2013)
Pesantren is a traditional Islamic educational institution whose purpose is to equip the students with tafaqquh fi> ad-di>n and al-akhla>q al-kar>imah to achieve success in the world as well as hereafter and to thrive in the countryside. Due to the demands of global development, pesantren runs modernized school salafi> to khalafi> to serve the community. Development is done by balancing religion and science as well as general science in their curriculum, which is done through formal education. Thus, pesantren always has development which keep space with the development era rhythm. This is consistent with the andegium they hold i.e. preserving good old things, as well as taking and developing new things which are better. Curriculum development is performed by adjusting the global demand, without leaving the tradition of reading “yellow book” as a dynamic space for the boards of the pesantren; so that the characteristics of the salafi pesantren is still maintained and the spirit of khalafi can be accommodated. Thus, pesantren develops a curriculum with an emphasis on Islamic values which aims are to form ‘abd Alla>h and khali>fah Alla>h fi> al-ard without leaving the matters concerning individual worldly needs.",